Oat avenanthramide-C (2c) is biotransformed by mice and the human microbiota into bioactive metabolites - Wang, Pei; Chen, Huadong; Zhu, Yingdong; McBride, Jennifer; Fu, Junsheng; Sang, Shengmin (The Journal of nutrition, 2015)
Avenanthramides (AVAs), which are found exclusively in oats, may play an important role in anti-inflammation and antiatherogenesis. Although the bioavailability of AVAs has been investigated previously, little is known about their metabolism. The aim of the present study was to investigate the metabolism of avenanthramide-C (2c), one of the major AVAs, in mice and by the human microbiota, as well as to elucidate the bioactivity of its major metabolites with the goal of finding new exposure markers to precisely reflect oat consumption. For the mouse study, 10 CF-1 female mice were divided into control (vehicle-treated) and 2c intragastrically treated (200 mg/kg) groups (5 mice/group). Twenty-four-hour urine and fecal samples were collected with use of metabolic cages. For the batch culture incubations, 2c was cultured with fecal slurries obtained from 6 human donors. Incubated samples were collected at various time points (0, 12, 24, 48, 72, 96, and 120 h). Metabolites were identified via HPLC with electrochemical detection and LC with electrospray ionization/mass spectrometry. To investigate whether 2c metabolites retain the biological effects of 2c, we compared their effects on the growth of and induction of apoptosis in HCT-116 human colon cancer cells. Eight metabolites were detected from the 2c-treated mouse urine samples. They were identified as 5-hydroxyanthranilic acid (M1), dihydrocaffeic acid (M2), caffeic acid (M3), dihydroferulic acid (M4), ferulic acid (M5), dihydroavenanthramide-C (M6), dihydroavenanthramide-B (M7), and avenanthramide-B (M8) via analysis of their MS(n) (n = 1-3) spectra. We found that the reduction of 2c's C7'-C8' double bond and the cleavage of its amide bond were the major metabolic routes. In the human microbiota study, 2c was converted into M1-M3 and M6. Moreover, interindividual differences in 2c metabolism were observed among the 6 human subjects. Subjects B, C, E, and F could rapidly metabolize 2c to M6, whereas subject D metabolized little 2c, even up to 120 h. In addition, only subjects A, B, and F could cleave the amide bond of 2c or M6 to form the cleaved metabolites. Furthermore, we showed that 2c and its major metabolite M6 are bioactive compounds against human colon cancer cells. M6 was more active than 2c with the half-inhibitory concentration (IC50) of 158 μM and could induce apoptosis at 200 μM. To our knowledge, the current study demonstrates for the first time that avenanthramide-C can be extensively metabolized by mice and the human microbiota to generate bioactive metabolites.